Salvia officinalis for Hot Flushes: Towards Determination of Mechanism of Activity and Active Principles - Rahte, Sinikka; Evans, Richard; Eugster, Philippe J.; Marcourt, Laurence; Wolfender, Jean-Luc; Kortenkamp, Andreas; Tasdemir, Deniz (Planta Medica, 2013)
Herbal medicinal products are commonly used in alternative treatment of menopausal hot flushes. In a recent clinical study, Salvia officinalis tincture was found to reduce hot flush frequency and intensity. The aim of the current study was the investigation of the mechanism(s) responsible for the anti-hot flush activity of S. officinalis and determination of its active principle(s). The 66 % ethanolic tincture, as well as the n-hexane, CHCl3, and aqueous ethanolic subextracts obtained from the tincture were studied in vitro for two of the most relevant activities, estrogenicity and selective serotonin reuptake inhibition. Because of an increased risk of menopausal women to suffer from Alzheimerʼs disease, an in vitro acetylcholinesterase inhibition assay was also employed. No activity was observed in the selective serotonin reuptake inhibition or the acetylcholinesterase inhibition assays at the highest test concentrations. The tincture showed no estrogenic effects whereas the aqueous ethanolic subextract exhibited estrogenicity in the ERLUX assay with an EC50 value of 64 µg/mL. Estrogenic activity-guided fractionation of the aqueous ethanolic subextract by a combination of reverse-phase vacuum liquid chromatography and gel chromatography identified luteolin-7-O-glucuronide (EC50 129 µg/mL) as the active component of the vacuum liquid chromatography fraction 4 (EC50 69 µg/mL). Luteolin-7-O-glucoside was identified as the putative estrogenic principle of the most potent minor fraction (7.6.7.6, EC50 0.7 µg/mL) obtained from the initial vacuum liquid chromatography fraction 7 (EC50 3 µg/mL). This study suggests the involvement of common and ubiquitous estrogenic flavonoids in the anti-hot flush effect of Salvia officinalis, a safe and commonly used herbal medicinal product during the menopause.
Keywords: estrogenicity; hot flush; luteolin-7-O-glucoside; menopause; Salvia officinalis; Lamiaceae